Probing the Structural Evolution and Stabilities of Medium-Sized MoBn0/– Clusters - Li, Peifang; Du, Xindi; Wang, Jing Jing; Lü, Cheng; Chen, Haihua (Journal of physical chemistry. C, 2018)
The intriguing electronic bonding properties of transition-metal-doped boron clusters have made them the subject of increased attention. However, the structures and stabilities of boron clusters doped with Mo remain elusive, and reports on Mo-doped boron clusters in the literature are still rare. Here, medium-sized MoBₙ⁰/– (n = 10–20) clusters were investigated by utilizing the unbiased CALYPSO structure searching method with subsequent DFT optimization at the PBE0/Mo/LANL2DZ/B/6-311+G(d) level. Three types of geometries were found for the ground-state structures of the MoBₙ⁰/– (n = 10–20) clusters: half-sandwich, drumlike, and tubular. Furthermore, the stability of the ground-state structures was quantified and analyzed based on three effective criteria. The simulated photoelectron spectra served as electronic “fingerprints” of the clusters for comparison with experimental spectra. Subsequent molecular orbital and adaptive natural density partitioning analyses revealed that the enhanced stability of MoB₁₈ resulted from strong interactions between the 4d orbitals of the Mo atoms and the 2p orbitals of the B atoms, as well as the B–B σ bonds in the B₁₈ shell.